Determinants of e-learning effectiveness among faculty of hotel and tourism students - Mohd Azhar, Fathonah; Abdul Majaid, Nur Zarith; Sulong, Siti Nurhanifah; Manshoor, Amir; Ideris, Muhamad Shah Kamal (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2025)
The rapid shift to online education has highlighted the importance of understanding factors that determine the effectiveness of e-learning, particularly in skill-based disciplines such as hospitality and tourism. A quantitative, correlational study was conducted, targeting university students with prior experience of using e-learning platforms within 3 months of data collection. Data were collected in Faculty of Hotel and Tourism Management, University Teknologi MARA (UiTM) Cawangan Terengganu and 318 valid responses were analyzed using SPSS. The reliability and validity of the data were confirmed. Descriptive analysis and Pearson correlation analysis were used to answered the objective of the study. The results revealed that all three factors were significantly and positively correlated with e-learning effectiveness, with perceived usefulness emerging as the strongest influence, followed by perceived ease of use and computer self-efficacy. The findings also provide practical implications for higher education institutions to design effective digital learning strategies, emphasizing user-friendly platforms and relevant content to support both theoretical and practical outcomes.